THE EFFECT OF TRANSFORMATIONAL LEADERSHIP, SOCIAL COMPETENCE, AND WORK DISCIPLINE ON PUBLIC SERVICE PERFORMANCE - As Ari; Laynita Sari (Yayasan Education and Social Center, 2026)
The purpose of this study was to determine the influence of transformational leadership, social competence, and work discipline on public service performance by the Keliling Danau Sub-district Head, Kerinci Regency. Based on the type of data, this study is quantitative. The data collection method used was a questionnaire, which was conducted by distributing a list of statements to respondents. The results of this study indicate that, both partially and simultaneously, the variables of transformational leadership, social competence, and work discipline have a positive and significant influence on public service performance by the Keliling Danau Sub-district Head, Kerinci Regency. The contribution of the variables of transformational leadership, social competence, and work discipline to performance is 77.9%.